HUBUNGAN ANTARA LAYANAN VIDEO ON DEMAND NETFLIX DAN MINAT BERLANGGANAN MAHASISWA - Lod Sulivyo (Program Studi Akuntansi, 2022)
This study has the aim of knowing and analyzing significantly whether there is a relationship between Netflix's Video On Demand Service and Student Subscription Interest by using several research variables to be analyzed, namely exogenous variables including Netflix Service (X1) and Technology Acceptance Model (X2) and Subscription Interest (Y) as endogenous variables. In this study, the acceptance model of the technology used includes the perception of ease of use, the perception of usability and the perception of price. The sample used was thirty-two students of the Ppi College of Economic Sciences. Analyzing the data obtained using Structural Equation Modelling Partial Least Square with the help of Smart PLS analysis tools. This study obtained the results of a positive influence of the Netflix Service variable and the Technology Acceptance Model (TAM) on student subscription interest, then the relationship between the Netflix Service variable to TAM and TAM on subscription interest resulted in a significant influence, but for the relationship between the Netflix Service variable to Subscription Interest did not have a significant influence.